Benefits and Barriers in EFL Learning and Teaching Across ASEAN Countries: A Systematic Literature Review (2021-2025) - Nicomedez, Jideah Nicole; Agpad, Donamae; Salbino, Kryshelle; Tawali, Mariel Kaye; Pelila, John Rey (Journal of Multidisciplinary Research and Development, 2026)
English is one of the most widely used languages in international communication, education, and employment; however, studies reveal gaps in understanding how EFL learning and teaching vary across ASEAN countries, particularly in balancing technological tools, teaching practices, and learner engagement. This study aimed to review the advantages and disadvantages of EFL learning and teaching in selected ASEAN contexts. A systematic literature review (SLR) was conducted, screening peer-reviewed articles published from 2021 to 2025 using databases such as ERIC and Taylor & Francis, resulting in 23 relevant studies. Deductive thematic analysis was employed to identify key patterns related to EFL advantages and challenges. The findings indicated that flexible learning, culturally relevant teaching practices, and technological innovations enhanced student engagement, language skills, and confidence. Conversely, digital barriers, insufficient teacher training, curriculum misalignment, and learners’ linguistic and psychological challenges hindered effective EFL learning. In conclusion, the success of EFL programs in ASEAN countries depends on coordinated, system-wide support integrating technology, pedagogy, and institutional resources. It is recommended that policymakers and educators invest in comprehensive support structures, culturally responsive curricula, and professional development to ensure equitable and effective English education across the region.